Effect of V addition on the hardness, adherence and friction coefficient of VC coatings produced by thermo-reactive diffusion deposition - Orjuela, Fredy Alejandro; Alfonso, Jose Edgar; Olaya, Jhon Jairo (DYNA, 2015)
Vanadium carbide (VC) coatings were deposited on AISI H13 and AISI D2 steel substrates via thermo-reactive deposition/diffusion (TRD) in order to evaluate their mechanical properties as a function of the vanadium content. The coatings were produced with different percentages of ferrovanadium in the reactive mixture. The chemical composition of the coatings was determined through X-ray fluorescence (XRF), the crystal structure was analyzed using X-ray diffraction (XRD), the morphology was characterized using scanning electron microscopy (SEM), the hardness was measured with nanoindention, and the tribological behavior was studied using the ball-on-disc test. The XRF analysis indicated that the coatings grown on D2 steel decreased the atomic percentage of vanadium when the coating was made with 20% ferrovanadium. The XRD analysis established that the coatings were polycrystalline, with a cubic structure. The SEM images revealed that the coatings grown on D2 steel were more compact than those grown on H13 steel. Finally, the wear tests established that the friction coefficient decreased with an increase of vanadium in the coating.